SELF DIRECTED LEARNING MODEL APPROACH - Balu, Fauzan; Olii, Rahmat; Paputungan, Frezy (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This research is a quasi-experimental study conducted to improve students' mathematical problem-solving abilities, one of which is through the use of the Self-Directed Learning (SDL) instructional model. The objectives of this study are to determine (a) the learning process using the Self-Directed Learning model; (b) the difference in improvement of students' mathematical problem-solving abilities between those using the Self-Directed Learning model and those receiving conventional (expository) instruction; and (c) students' attitudes toward mathematics learning using the Self-Directed Learning model. Data were collected using research instruments including tests in the form of mathematical problem-solving ability questions and non-tests such as student response questionnaires toward learning using the Self-Directed Learning model. This study was conducted at MAN 1 Gorontalo, with class X IPA-1 as the experimental class and class X IPA-2 as the control class, focusing on vector material. Based on the research results and n-gain data analysis, it was found that: (a) the description of the teacher and student learning process on quadrilateral vector material using the Self-Directed Learning model falls into the good category; (b) the improvement in mathematical problem-solving ability of students who received learning with the Self-Directed Learning model showed a moderate increase. Meanwhile, the improvement in mathematical problem-solving ability of students who received conventional learning showed a low increase. Therefore, there is a difference in the improvement of mathematical problem-solving ability between students using the Self-Directed Learning model and those using conventional learning; (c) most students who received learning using the Self-Directed Learning model responded positively to mathematics learning using this model.